Treatment strategies to combat antimicrobial resistance in ‎gastrointestinal infections - Qassadi, Fatimah (2024)
The growing threat of antimicrobial resistance (AMR) necessitates the exploration of ‎antibacterial therapeutic strategies to treat bacterial infections. This thesis explores metabolic ‎targets for conventional and emerging therapies aimed at gastrointestinal (GI) infections ‎caused by Escherichia coli (E. coli) and Clostridioides difficile (C. difficile). The research ‎evaluates plant-based natural compound such as berberine, conventional antibiotics like ‎azithromycin, and microbiome-based therapies including bacteriophages, bacteriophages ‎combined with azithromycin, faecal microbiota transplantation (FMT) and faecal filtrates ‎derived from FMT donors. Bacterial metabolic processes play a key role in cellular function and is closely associated with ‎AMR mechanisms. Metabolomics has become an increasingly popular “omics” approach for ‎understanding the underlying biological mechanisms related to AMR and for identifying ‎important metabolic pathways and biomarkers. By characterising the metabolic profiles of ‎bacteria, their responses to different therapeutics can be elucidated, facilitating the ‎identification of previously unexplored therapeutic targets. This thesis demonstrates the use ‎of Liquid chromatography-mass spectrometry (LC-MS) and Orbitrap secondary ion mass ‎spectrometry (OrbiSIMS) to assess the effectiveness of these therapies and identify molecular ‎targets and metabolic pathways related to treatment responses. The study first examines the differential abundance of metabolites in pathogenic multidrug ‎resistant (MDR) enteroaggregative E. coli (EAEC O104:H4) compared to non-pathogenic E. ‎coli O157: H7 (B6914) strains. Mass spectrometry (MS)-based metabolomic analysis revealed ‎significant differences in bacterial metabolomes. The ‎results showed that the metabolome of ‎pathogenic E. coli differs significantly from that of non-pathogenic E. coli. Several pathways ‎with significant associations to ‎bacterial resistance were identified, notably alterations in ‎amino acid biosynthesis, tricarboxylic acid (TCA) cycle intermediates, and ‎phosphatidylglycerol ‎lipids, making them potential therapeutic targets.‎ Natural source-based antibacterial agents, including plant-derived compounds, are re-gaining ‎interest due to their diverse mechanisms of action and potential against MDR pathogens. This ‎thesis investigates the antimicrobial activity and the metabolic alterations induced by ‎berberine in both pathogenic MDR EAEC O104:H4 and non-pathogenic E. coli O157: H7 ‎strains. The metabolomic analyses revealed that berberine disrupts key metabolic pathways, ‎including the TCA cycle and peptidoglycan biosynthesis, compromising bacterial membrane integrity. The ‎metabolomics data further revealed a significant depletion of glutathione, a key antioxidant ‎that neutralises reactive oxygen species (ROS) and maintains cellular redox balance. These ‎disruptions were supported by ROS generation assays, resulting in significant oxidative stress. ‎These metabolic pathways are essential for bacterial viability and could serve as metabolic ‎targets for berberine’s antibacterial activity.‎ The investigation into azithromycin's mode of action revealed off-target related effects ‎beyond its well-known role in inhibiting protein synthesis. This study uniquely employed a ‎complementary metabolomics approach using both OrbiSIMS and LC-MS to evaluate ‎azithromycin-induced metabolic changes in MDR pathogenic and non-pathogenic E. ‎coli strains. Pathogenic strain exhibited specific alterations in the glutamate-glutamine cycle, ‎while non-pathogenic strain showed changes in arginine biosynthesis. The integration of ‎OrbiSIMS and LC-MS platforms provided comprehensive coverage of amino acids and lipid ‎metabolites while validating the significant metabolic changes observed in OrbiSIMS data.‎ When combined with bacteriophage therapy (vB_EcoM_SVMS_56), azithromycin ‎demonstrated a synergistic effect, particularly in disrupting branched-chain amino acids ‎‎(BCAAs) biosynthesis and phospholipid metabolism. Membrane phospholipid alterations, ‎observed through OrbiSIMS, suggest an adaptation mechanism to counteract azithromycin ‎and phage-induced stress. The profiling of the bacterial samples with OrbiSIMS allowed for ‎spatial distribution and mapping of the biomolecules in depth. The discriminative metabolites ‎were spatially localised, showing that phospholipids were concentrated near the surface of the ‎bacterial cells. These lipids are the major components of the membrane and are highly ‎enriched at the surface of cells. BCAAs were detected throughout sample depth, emphasising ‎the capability of OrbiSIMS for precise metabolic mapping.‎ This thesis also explores the potential of FMT for treating GI infections caused by MDR ‎EAEC and toxigenic C. difficile. OrbiSIMS-based metabolomic analysis of faecal samples ‎from patients with C. difficile infections (n =12; average age 63.8 years, 67% female), ‎collected either before or 12-weeks after FMT, revealed significant changes in key ‎metabolites, including those involved in glycosylphosphatidylinositols biosynthesis. ‎Furthermore, the impact of faecal filtrates derived from FMT of healthy donors (n = 4; 2 ‎males and 2 females; mean [Standard deviation (SD)] age, 33 [2.3] years) on the metabolomes ‎of pathogenic bacterial strains, including EAEC (O104:H4 and O20:H19) and toxigenic C. ‎difficile (VPI 10463 and ‎CD630), was investigated. The metabolic changes induced by faecal filtrate were strain-‎specific, with significant alterations in glycerophospholipid metabolism and metabolites ‎modulating pathogenicity and virulence such as isoleucine, proline and fumarate. OrbiSIMS ‎enabled not only the detection but also the imaging of these essential metabolites, providing ‎critical insights into their localisation and distribution.‎ The identification of metabolic signatures and biomarkers through MS-based metabolomic ‎approaches could guide the development of more effective and targeted therapeutic strategies ‎against GI infections and drug-resistant pathogens.‎